Profil Literasi ICT dalam Pembelajaran IPA Berbantuan Google-Sites pada Peserta Didik SMP - Imesta Zulfanida Ernest; Suyanta Suyanta (Postgraduate, University of Mataram, 2024)
Education in the era of revolution must utilize the application of ICT in science learning which can refer to 21st- century skills is ICT literacy. The purpose of this study aims to see the effect of Google sites-based science learning on the profile of ICT literacy of junior high school students. The method used is quantitative research by giving post-tests to two different classes that have implemented the learning The two classes consisted of the experiment class and the control class. The sampling technique used was cluster random sampling. The results obtained were then analyzed and discussed descriptively quantitative. The results show that the application of Google sites-based learning can affect the achievement of students' ICT literacy profile by obtaining an average score of high categories in the experiment class and medium category in the control class. Based result of study, there is a significant influence of the use of Google-sited based in science learning on ICT literacy in junior high school students